Relationship between body height and the length of canine teeth in terms of jaw and Gender using the CBCT technique in patients. (June 2020) - Shalakizadeh, Mohsen; Razi, Tahmineh; Emamverdizadeh, Parya; Razi, Sedigheh
Highlights: Canine teeth show the most important gender dimorphism among the teeth. Tooth sizes have a polygenetic nature and can continually change. Individuals from different ethnic origins have different morphological characteristics. Abstract: Introduction: One of the critical factors in identifying individuals is the relationship between the size of different parts of the body and the body height, which has been considered by forensic medicine investigators in the past two decades. Considering that canine teeth show the most important gender dimorphism among the teeth, this study aimed to determine the relationship between the body height and the length of canine teeth in terms of the jaw and gender using the cone-beam computed tomography (CBCT). Materials and methods: In this cross-sectional study, CBCT images of 133 patients referring to Tabriz Dental School for various reasons were selected and evaluated. The demographic characteristics of individuals, including age and gender, were recorded. Then the height of the subjects was measured in the standing position with the Frankfort plane parallel to the floor. Then the canine teeth were measured on the CBCT images. Data were analyzed with SPSS 17. The significance level of the study was P<0.05. Results: The mean length of canine teeth in the maxilla of males was 28.18 mm, with 25.84, 25.39 and 24.03 mm in the mandible of males, the maxilla of females and the mandible of females, respectively. The results of statistical analyses showed a significant difference between the mean length of canine in both genders and both the maxilla and mandible (P<0.001). Conclusion: In both genders, maxillary canines were longer than the mandibular canines. There was a correlation between the maxillary canine length and the height of the female subjects.